The moral foundations of criminal responsibility - Peno, Michał (Acta Universitatis Lodziensis. Folia Iuridica, 2015)
The subject matter of this paper are moral problems of criminal liability, with a particular focus on an attempt to find such features in the area of morality whose accumulation in criminal law determines its specificity. We may distinguish two aspects of deliberations on moral problems of criminal liability. The first of the aspects concerns the issue whether all behaviours regarded as criminal offences are morally wrong. It is particularly important as such condemnation of the act is supposed to distinguish criminal law from other branches of public law. The second aspect concerns the issue of criminal penalty and it is related to the issue of guilt and its relationship with moral responsibility. The main argument of this paper is the fact that the contemporary philosophy of law has not created any coherent concept making it possible to distinguish criminal law from other branches of public law on grounds of morality.